If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-2(x+6)=x+6
We move all terms to the left:
3-2(x+6)-(x+6)=0
We multiply parentheses
-2x-(x+6)-12+3=0
We get rid of parentheses
-2x-x-6-12+3=0
We add all the numbers together, and all the variables
-3x-15=0
We move all terms containing x to the left, all other terms to the right
-3x=15
x=15/-3
x=-5
| (x-5)/3=4(1/4x-3)-2/3x | | 20.4x=232.56 | | 12(y+3)=5(2y-7 | | 5x^2+25x-10=0 | | p=-1+1/2.5 | | 5(5a+5)-4a=-14+8a | | 2w+17=37 | | 5(-7x-7)=-175 | | 2x-3=3x-12 | | x-26=-38 | | -93=-3(-4p-1) | | 3=3+x-x+0 | | x/8-8=-4 | | 5.51=6.6-v | | 8−2d=2d= | | 45.3n=–181.2 | | 20n-28=10n | | 8−2d= | | 3x-6+1=2x-5=5x | | 8x-3=-39 | | -20=-2+3y | | 8x+5=1x+4 | | 205=29-w | | 6+x/9=-1 | | 14-6x=7+43x | | 5(r-1)=5r-7 | | -12+x=1-4x+7 | | 81=2x+7x | | 16=10w-8w | | 23(x)-5=14x | | -4(6v+6)=-216 | | n/6−38=-33 |